2021
DOI: 10.1038/s41598-021-81524-w
|View full text |Cite
|
Sign up to set email alerts
|

Reference gene selection for qRT-PCR analyses of luffa (Luffa cylindrica) plants under abiotic stress conditions

Abstract: Selecting suitable internal reference genes is an important prerequisite for the application of quantitative real-time PCR (qRT-PCR). However, no systematic studies have been conducted on reference genes in luffa. In this study, seven reference genes were selected, and their expression levels in luffa plants exposed to various simulated abiotic stresses [i.e., cold, drought, heat, salt, H2O2, and abscisic acid (ABA) treatments] were analyzed by qRT-PCR. The stability of the reference gene expression levels was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Stem-loop qPCR analysis showed that the expression level of mature miR319 was rapidly upregulated after 6 h of LT treatment, but decreased to control (0 h) level after 24 h ( Figure 6 B). Some studies have shown the EF-1α was sufficient for accurate normalization in cold-treated samples, and the EF-1α gene was the frequently-used internal control in the genus chrysanthemum for normalizing transcription data [ 70 , 71 , 72 ]. When performing microRNA detection, because a better strategy is choosing a constitutively expressed small noncoding RNA as a reference, we often chose the U6 gene [ 73 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Stem-loop qPCR analysis showed that the expression level of mature miR319 was rapidly upregulated after 6 h of LT treatment, but decreased to control (0 h) level after 24 h ( Figure 6 B). Some studies have shown the EF-1α was sufficient for accurate normalization in cold-treated samples, and the EF-1α gene was the frequently-used internal control in the genus chrysanthemum for normalizing transcription data [ 70 , 71 , 72 ]. When performing microRNA detection, because a better strategy is choosing a constitutively expressed small noncoding RNA as a reference, we often chose the U6 gene [ 73 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a study aiming to screen out suitable reference genes in two thyme species (Lamiaceae family), recommended GAPDH and 18S rRNA as the best and the worst genes, respectively [ 24 ]. Much research has also demonstrated that the expression levels of reference genes might vary not only within tissues or development stages but also even get influenced by various biotic and abiotic stresses [ 7 , 26 ]. For example, a study with genome-wide identification and assessment of novel reference genes in wheat identified stable expression for ACT and UBQ , but not in tomato plants [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elongation factor 1α ( EF-1α ) (MN548044) was used as a housekeeping gene (internal control), previously reported by Chen [ 53 ]. ABI PRISM 7900HT sequence detection system (Applied Biosystems Applera, Darmstadt, Germany) was used for gene amplification and real-time detection.…”
Section: Methodsmentioning
confidence: 99%